Crosslinguistic influence and L2 grammar learning: Proposed replications of Ellis and Sagarra (2011) and Tolentino and Tokowicz (2014). (October 2022) - McManus, Kevin
Abstract: Investigations of crosslinguistic effects in second language acquisition (SLA) have contributed rich understandings about the ways in which prior language knowledge and experience can influence additional language learning. Building on this work, one recent line of research has examined the extent to which SLA findings about crosslinguistic influence can be used to improve L2 learning, indicating that explicit instruction tailored to address the nature of the crosslinguistic learning problem can benefit L2 performance. At the same time, however, this line of inquiry is relatively novel and under-researched. The aim of this paper, therefore, is to suggest further research which might advance knowledge and understanding about the ways in which explicit instruction can facilitate second language (L2) learning of crosslinguistically difficult target features. To this end, I lay the ground for a series of close replications designed to understand the role of prior language knowledge and experience in L2 learning: Ellis and Sagarra (2011 ) and Tolentino and Tokowicz (2014 ). These studies were selected because they are grounded in empirical SLA research and SLA theory. In addition, the selected studies facilitate replication because they have either (i) made their data collection materials available in digital repositories or (ii) have robustly described their design and provided the stimuli used.